HUBUNGAN BURNOUT DENGAN KUALITAS TIDUR MAHASISWA TINGKAT AKHIR FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH - Intan Sesri Winarni; Melya Susanti; Revivo Rinda Pratama (Nusantara Hasana Journal, 2025)
Final-year medical students are often exposed to substantial academic demands, the obligation to complete a thesis, and the transition to professional practice. These conditions may trigger burnout, characterized by physical and psychological exhaustion resulting from chronic stress. Burnout can affect multiple aspects of life, particularly sleep quality, which plays a crucial role in maintaining cognitive function, physical health, and psychological well-being. This study aimed to evaluate the association between burnout and sleep quality among final-year medical students at the Faculty of Medicine, Universitas Baiturrahmah. An analytical observational study with a cross-sectional design was conducted. Primary data were collected from 55 respondents using questionnaires. Univariate analysis was presented in frequency distributions, while the chi-square test was employed to examine the association between variables. Among the participants, 33 students (60.0%) were identified as experiencing burnout, while poor sleep quality was reported in 41 students (74.5%). Statistical analysis demonstrated a significant association between burnout and sleep quality (p = 0.032; p < 0.05). Burnout is significantly associated with poor sleep quality among final-year medical students. These findings highlight the need for preventive strategies that integrate stress management and interventions targeting sleep quality.